2007
DOI: 10.1038/sj.jhh.1002249
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns of hypertension and dyslipidaemia in hypertensive patients at higher and lower risk of cardiovascular disease in primary care in the United Kingdom

Abstract: Few studies have investigated the presence of dyslipidaemia in hypertensive individuals. In addition, few data exist on the concurrent treatment of both conditions for the prevention of cardiovascular disease (CVD). This retrospective cohort study examined treatment patterns for hypertension and dyslipidaemia among hypertensive patients in UK primary care. We defined a population of patients aged X40 years from the UK General Practice Research Database. Hypertensive individuals with X3 additional cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…This is similar to the findings of a study conducted in the United Kingdom (13) that suggested the presence of a gap in the clinical care for hypertension; in particular, missed opportunities to detect and prevent CVD and TOD. This gap could have a negative impact on the morbidity and mortality of such patients.…”
Section: Discussionsupporting
confidence: 79%
“…This is similar to the findings of a study conducted in the United Kingdom (13) that suggested the presence of a gap in the clinical care for hypertension; in particular, missed opportunities to detect and prevent CVD and TOD. This gap could have a negative impact on the morbidity and mortality of such patients.…”
Section: Discussionsupporting
confidence: 79%
“…Undertreatment of CV comorbidities is a commonly encountered problem in clinical practice and has also been observed in nonpsoriasis populations, including patients with diabetes, 43 high-risk dyslipidemic patients with or without established CV disease, 44,45 and high-risk hypertensive patients. 46 Similar findings have also been reported for patients with lupus and RA. In one study, only 23% of patients with lupus had lipid panels determined and only 21% of those with hypercholesterolemia were receiving treatment.…”
Section: Discussionsupporting
confidence: 73%
“…These two conditions, among others, increase CVD risk and there is an absolute necessity to effectively treat all CVD risk factors, among which is dyslipidemia. Similar data are reported by the CEPHEUS South Africa Study 6 , the CEPHEUS Pan-Asia Study 7 , the CEPHEUS Centralized Pan-European Study 8 and other European Countries 9 as well as the OLYMPIC and the metabolic syndrome Greece (n ¼ 10,000) studies 10,11 , a study from the UK (n ¼ 117,840) 12 and a study from the US National Health and Nutrition Examination Survey 13 . The recent Euroaspire IV 14 included high risk individuals (coronary patients) from 26 countries 14 .…”
supporting
confidence: 67%